Assessment of the Department of Veterans Affairs Airborne Hazards and Open Burn Pit Registry - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Military operations produce a great deal of trash in an environment where standard waste management practices may be subordinated to more pressing concerns. As a result, ground forces have long relied on incineration in open-air pits as a means of getting rid of refuse. Concerns over possible adverse effects of exposure to smoke from trash burning in the theater were first expressed in the wake of the 1990–1991 Gulf War and stimulated a series of studies that indicated that exposures to smoke from oil-well fires and from other combustion sources, including waste burning, were stressors for troops. In January 2013, Congress directed the Department of Veterans Affairs (VA) to establish and maintain a registry for service members who may have been exposed to toxic airborne chemicals and fumes generated by open burn pits. Assessment of the Department of Veterans Affairs Airborne Hazards and Open Burn Pit Registry analyzes the initial months of data collected by the registry and offers recommendations on ways to improve the instrument and best use the information it collects. This report assesses the effectiveness of the VA's information gathering efforts and provides recommendations for addressing the future medical needs of the affected groups, and provides recommendations on collecting, maintaining, and monitoring information collected by the VA's Airborne Hazards and Open Burn Pit Registry.
Keywords: Health and Medicine; Environment and Environmental Studies

Accomplishments of the U.S. Global Change Research Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The U.S. Global Change Research Program (USGCRP) is an interagency program, established by the Global Change Research Act (GCRA) of 1990, mandated by Congress to "assist the Nation and the world to understand, assess, predict, and respond to human-induced and natural processes of global change". Since the USGCRP began, scientific understanding of global change has increased and the information needs of the nation have changed dramatically. A better understanding of what is changing and why can help decision makers in the public and private sectors cope with ongoing change. Accomplishments of the U.S. Global Change Research Program highlights the growth of global change science in the quarter century that the USGCRP has been in existence, and documents some of its contributions to that growth through its primary functions of interagency planning and coordination, and of synthesis of research and practice to inform decision making.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies; Earth Sciences

Lessons Learned from Diverse Efforts to Change Social Norms and Opportunities and Strategies to Promote Behavior Change in Behavioral Health: Proceedings of Two Workshops - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In 2015, the National Academies of Sciences, Engineering, and Medicine convened two workshops with oversight from the Committee on the Science of Changing Behavioral Health Social Norms. The workshops provided input to the committee’s deliberations and contributed to the development of the report Ending Discrimination against People with Mental and Substance Use Disorders. That report was issued to help the Substance Abuse and Mental Health Services Administration and the Office of the Assistant Secretary for Planning and Evaluation, U.S. Department of Health and Human Services, utilize the scientific evidence base in improving public attitudes toward and understanding of behavioral health, specifically in the areas of mental health and substance use disorders. This publication summarizes the presentations and discussions at the two workshops.
Keywords: Behavioral and Social Sciences

Liability of State Departments of Transportation for Design Errors - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Legal Research Digest 74: Liability of State Departments of Transportation for Design Errors covers liability insurance for design errors and omissions. It also examines public construction law, professional liability, and product warranties. This study demonstrates that litigation has defined the parameters of a transportation department’s liability for design errors or omissions. State tort- and sovereign-immunity statutes may shield an agency from liability. If the state has waived its immunity for certain claims, however, the transportation department may still have immunity when it has exercised discretion in the planning or design phase of a project. When a government contractor is acting as an agent of the transportation agency, the contractor may also have a claim. If a contractor is at fault, the agency may be able to recoup any related losses incurred from the contractor. Appendixes A-E and Appendix F are available via online.
Keywords: Transportation and Infrastructure

Building a National Capability to Monitor and Assess Medical Countermeasure Use During a Public Health Emergency: Going Beyond the Last Mile: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
During public health emergencies (PHEs) involving chemical, biological, radiological, or nuclear threats or emerging infectious diseases, medical countermeasures (MCMs) (e.g., drugs, vaccines, devices) may need to be dispensed or administered to affected populations to help mitigate the human health impact of the threat. The optimal MCMs determined for use during an emergency might be U.S. Food and Drug Administration (FDA) approved but used in unapproved ways (e.g., in a new age group or against a new agent); FDA approved using animal models because human efficacy testing is not ethical or feasible; or not yet FDA approved for any indication. As part of the United States’ scientific and research preparedness enterprise, there is an imperative to go “beyond the last mile” of MCM dispensing and administration to build and maintain a national capability to monitor and assess the use of MCMs (e.g., safety, compliance, clinical benefit) after they have been dispensed during PHEs. To further the discussion on this need, the Board on Health Sciences Policy of the National Academies of Sciences, Engineering, and Medicine hosted a 2-day public workshop, Building a National Capability to Monitor and Assess Medical Countermeasure Use in Response to Public Health Emergencies. The workshop, sponsored by FDA, was held on June 6–7, 2017, in Washington, DC. Workshop participants discussed the roles and efforts of the federal government and of relevant stakeholders with an interest in building and maintaining a national PHE MCM active monitoring and assessment capability. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Valuing Climate Damages: Updating Estimation of the Social Cost of Carbon Dioxide - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The social cost of carbon (SC-CO2) is an economic metric intended to provide a comprehensive estimate of the net damages - that is, the monetized value of the net impacts, both negative and positive - from the global climate change that results from a small (1-metric ton) increase in carbon-dioxide (CO2) emissions. Under Executive Orders regarding regulatory impact analysis and as required by a court ruling, the U.S. government has since 2008 used estimates of the SC-CO2 in federal rulemakings to value the costs and benefits associated with changes in CO2 emissions. In 2010, the Interagency Working Group on the Social Cost of Greenhouse Gases (IWG) developed a methodology for estimating the SC-CO2 across a range of assumptions about future socioeconomic and physical earth systems. Valuing Climate Changes examines potential approaches, along with their relative merits and challenges, for a comprehensive update to the current methodology. This publication also recommends near- and longer-term research priorities to ensure that the SC- CO2 estimates reflect the best available science.
Keywords: Environment and Environmental Studies

Exploring the Translation of the Results of Hurricane Sandy Research Grants into Policy and Operations: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The workshop Translating the Results of Hurricane Sandy Research Grants into Policy and Operations was convened on July 20, 2017, in Washington, DC, by the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine. Workshop participants explored key findings from published Hurricane Sandy research grant projects, examined the impact of the scientific findings on disaster policy and operations, and discussed opportunities to translate the research findings to future preparedness response and recovery efforts. The workshop included panel sessions focused on the potential policy and operational implications from research on mental health, public health, access to care, and primary care. An additional “marketplace” session gave researchers, operations agents, and policy experts an opportunity to discuss particular research findings and how they might be applied to operations and policy. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Principles and Practices for Federal Program Evaluation: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In October 2016 the National Academies of Sciences, Engineering, and Medicine held a 1-day public workshop on principles and practices for federal program evaluation. Participants focused on reviews of existing policies of the Administration for Children and Families, the Institute for Education Sciences, the Chief Evaluation Office in the U.S. Department of Labor, and other federal agencies. The scope of the workshop included evaluations of interventions, programs, and practices intended to affect human behavior, carried out by the federal government or its contractual agents and leading to public reports intended to provide information on impacts, cost, and implementation. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

Multisector Community Health Partnerships: Potential Opportunities and Challenges: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On December 8, 2016, the Roundtable on Population Health Improvement held a 1-day public workshop in Oakland, California. At this workshop, participants explored multisector community health partnerships that aim to address inequities and improve the health and well-being of communities. Individual participants discussed different strategies used by community partnerships to engage residents in community health initiatives. This publication highlights topics that individual speakers identified as opportunities and challenges to engaging a range of residents and other stakeholders in community-driven social change.
Keywords: Health and Medicine

Training the Future Child Health Care Workforce to Improve the Behavioral Health of Children, Youth, and Families: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Increasing numbers of evidence-based interventions have proven effective in preventing and treating behavioral disorders in children. However, the adoption of these interventions in the health care system and other systems that affect the lives of children has been slow. Moreover, with few exceptions, current training in many fields that involve the behavioral health of children falls short of meeting the needs that exist. In general, this training fails to recognize that behavioral health disorders are among the largest challenges in child health and that changing cognitive, affective, and behavioral health outcomes for children will require new and more integrated forms of care at a population level in the United States. To examine the need for workforce development across the range of health care professions working with children and families, as well as to identify innovative training models and levers to enhance training, the Forum on Promoting Children’s Cognitive, Affective, and Behavioral Health held a workshop in November 2016. Workshop panelists and participants discussed the needs for workforce development across the range of health care professions working with children, youth, and families, and identified innovative training models and levers for change to enhance training. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences

Strategies to Limit Sugar-Sweetened Beverage Consumption in Young Children: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On June 21–22, 2017, the National Academies of Sciences, Engineering, and Medicine’s Food and Nutrition Board convened a workshop in Washington, DC, to explore the range of policies and programs that exist at the federal, state, tribal, and local levels to limit sugar-sweetened beverage consumption in children birth to 5 years of age. Topics examined over the course of the 1.5-day workshop included prevalence and trends in beverage intake among young children; beverage intake guidelines applicable to the age range of interest; challenges and opportunities of influencing beverage consumption; the role of industry in beverage intake; and knowledge gaps and research needs. This publication highlights key points made by individual speakers during the presentations and discussions.
Keywords: Food and Nutrition; Health and Medicine

Methods and Technologies for Pedestrian and Bicycle Volume Data Collection: Phase 2 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Web-Only Document 229: Methods and Technologies for Pedestrian and Bicycle Volume Data Collection: Phase 2 explores automated count technologies that capture pedestrian and bicycle volume data. The publication focuses on technologies that came onto the market too late to be included in previous Phase 1 research. Findings from Phase 1 are documented in NCHRP Report 797: Guidebook on Pedestrian and Bicycle Volume Data Collection and NCHRP Web-Only Document 205: Methods and Technologies for Pedestrian and Bicycle Volume Data Collection.The report presents combined results for a range of technologies tested by both the Phase 1 research and the continuation research (Phase 2). The research evaluated automated nonmotorized count technologies in different settings, including ranges of temperature, varying weather conditions, mixed traffic conditions, mixed travel directions, and facility types (e.g., roadways, multiuse paths), to determine their accuracy and reliability in different contexts. This report documents the research findings on the accuracy and consistency found for the different automated count technologies. It provides an account of the process used to select technologies for testing, identifies test sites, and evaluates the effectiveness of the technologies.
Keywords: Transportation and Infrastructure

Seeing Students Learn Science: Integrating Assessment and Instruction in the Classroom - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Science educators in the United States are adapting to a new vision of how students learn science. Children are natural explorers and their observations and intuitions about the world around them are the foundation for science learning. Unfortunately, the way science has been taught in the United States has not always taken advantage of those attributes. Some students who successfully complete their K–12 science classes have not really had the chance to "do" science for themselves in ways that harness their natural curiosity and understanding of the world around them. The introduction of the Next Generation Science Standards led many states, schools, and districts to change curricula, instruction, and professional development to align with the standards. Therefore existing assessments—whatever their purpose—cannot be used to measure the full range of activities and interactions happening in science classrooms that have adapted to these ideas because they were not designed to do so. Seeing Students Learn Science is meant to help educators improve their understanding of how students learn science and guide the adaptation of their instruction and approach to assessment. It includes examples of innovative assessment formats, ways to embed assessments in engaging classroom activities, and ideas for interpreting and using novel kinds of assessment information. It provides ideas and questions educators can use to reflect on what they can adapt right away and what they can work toward more gradually.
Keywords: Education

Strengthening the Workforce to Support Community Living and Participation for Older Adults and Individuals with Disabilities: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
As the demographics of the United States shift toward a population that is made up of an increasing percentage of older adults and people with disabilities, the workforce that supports and enables these individuals is also shifting to meet the demands of this population. For many older adults and people with disabilities, their priorities include maximizing their independence, living in their own homes, and participating in their communities. In order to meet this population’s demands, the workforce is adapting by modifying its training, by determining how to coordinate among the range of different professionals who might play a role in supporting any one older adult or individual with disabilities, and by identifying the ways in which technology might be helpful. To better understand how the increasing demand for supports and services will affect the nation’s workforce, the National Academies of Sciences, Engineering, and Medicine convened a public workshop in June 2016, in Washington, DC. Participants aimed to identify how the health care workforce can be strengthened to support both community living and community participation for adults with disabilities and older adults. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences

Integrating the Patient and Caregiver Voice into Serious Illness Care: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Millions of people—infants, children, adults, and their families—are currently coping with serious illness in the United States. Efforts are intensifying to improve overall care quality through the delivery of person-centered and family-oriented services, for patients of all ages and across disease stages, care settings, and specialties. While aging Baby Boomers are increasing the proportion of patients in the Medicare population over time, the sickest and most vulnerable patients needing health system support and other services to meet their complex needs can be found across the age spectrum and in a broad range of care settings, from perinatal care to geriatric care. Recognizing the need to thoughtfully consider and address the challenges and opportunities in efforts to improve care quality and value, the Roundtable on Quality Care for People with Serious Illness of the National Academies of Sciences, Engineering, and Medicine held the public workshop Integrating the Patient and Caregiver Voice into Serious Illness Care, on December 15, 2016, in Washington, DC. This workshop was the first in a series planned by the roundtable, and was designed specifically to bring together diverse personal perspectives and experiences about priorities and values that are important to patients and families coping with serious illness, and to consider solutions that support integration of these priorities and values in practice. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Review of the Research Program of the U.S. DRIVE Partnership: Fifth Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Review of the Research Program of the U.S. DRIVE Partnership: Fifth Report follows on four previous reviews of the FreedomCAR and Fuel Partnership, which was the predecessor of the U.S. DRIVE Partnership. The U.S. DRIVE (Driving Research and Innovation for Vehicle Efficiency and Energy Sustainability) vision, according to the charter of the Partnership, is this: American consumers have a broad range of affordable personal transportation choices that reduce petroleum consumption and significantly reduce harmful emissions from the transportation sector. Its mission is as follows: accelerate the development of pre-competitive and innovative technologies to enable a full range of efficient and clean advanced light-duty vehicles (LDVs), as well as related energy infrastructure. The Partnership focuses on precompetitive research and development (R&D) that can help to accelerate the emergence of advanced technologies to be commercialization-feasible. The guidance for the work of the U.S. DRIVE Partnership as well as the priority setting and targets for needed research are provided by joint industry/government technical teams. This structure has been demonstrated to be an effective means of identifying high-priority, long-term precompetitive research needs for each technology with which the Partnership is involved. Technical areas in which research and development as well as technology validation programs have been pursued include the following: internal combustion engines (ICEs) potentially operating on conventional and various alternative fuels, automotive fuel cell power systems, hydrogen storage systems (especially onboard vehicles), batteries and other forms of electrochemical energy storage, electric propulsion systems, hydrogen production and delivery, and materials leading to vehicle weight reductions.
Keywords: Energy and Energy Conservation; Transportation and Infrastructure

Powering Science: NASA's Large Strategic Science Missions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
NASA's Science Mission Directorate (SMD) currently operates over five dozen missions, with approximately two dozen additional missions in development. These missions span the scientific fields associated with SMD's four divisions—Astrophysics, Earth Science, Heliophysics, and Planetary Sciences. Because a single mission can consist of multiple spacecraft, NASA-SMD is responsible for nearly 100 operational spacecraft. The most high profile of these are the large strategic missions, often referred to as "flagships." Large strategic missions are essential to maintaining the global leadership of the United States in space exploration and in science because only the United States has the budget, technology, and trained personnel in multiple scientific fields to conduct missions that attract a range of international partners. This report examines the role of large, strategic missions within a balanced program across NASA-SMD space and Earth sciences programs. It considers the role and scientific productivity of such missions in advancing science, technology and the long-term health of the field, and provides guidance that NASA can use to help set the priority of larger missions within a properly balanced program containing a range of mission classes.
Keywords: Space and Aeronautics

Guidelines for Optimizing the Risk and Cost of Materials QA Programs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Report 838: Guidelines for Optimizing the Risk and Cost of Materials QA Programs proposes guidelines for optimizing the risk and cost of materials quality assurance (QA) programs. It develops a methodology for establishing a materials QA program that optimizes risk and cost by providing appropriate types, levels, and frequencies of agency testing and inspection for transportation projects across their full range of type, size, complexity, and project-delivery method.
Keywords: Transportation and Infrastructure

Strategies to Limit Sugar-Sweetened Beverage Consumption in Young Children: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On June 21–22, 2017, the National Academies of Sciences, Engineering, and Medicine's Food and Nutrition Board convened a workshop in Washington, DC, to explore the range of policies and programs that exist at the federal, state, tribal, and local levels to limit sugar-sweetened beverage consumption in children birth to 5 years of age. Topics examined over the course of the 1.5-day workshop included prevalence and trends in beverage intake among young children; beverage intake guidelines applicable to the age range of interest; challenges and opportunities of influencing beverage consumption; the role of industry in beverage intake; and knowledge gaps and research needs. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Engineering Societies and Undergraduate Engineering Education: Proceedings of a Workshop - National Academy of Engineering (The National Academies Press, 2017)
Engineering professional societies in the United States are engaged in a wide range of activities involving undergraduate education. However, these activities generally are not coordinated and have not been assessed in such a way that information about their procedures and outcomes can be shared. Nor have they been assessed to determine whether they are optimally configured to mesh with corresponding initiatives undertaken by industry and academia. Engineering societies work largely independently on undergraduate education, leaving open the question of how much more effective their efforts could be if they worked more collaboratively—with each other as well as with academia and industry. To explore the potential for enhancing societies’ role at the undergraduate level, the National Academy of Engineering held a workshop on the engagement of engineering societies in undergraduate engineering education. This publication summarizes the presentations and discussions from the workshop.
Keywords: Engineering and Technology